2016
DOI: 10.1016/j.celrep.2016.06.100
|View full text |Cite
|
Sign up to set email alerts
|

Chx10 Consolidates V2a Interneuron Identity through Two Distinct Gene Repression Modes

Abstract: During development, two cell types born from closely related progenitor pools often express identical transcriptional regulators despite their completely distinct characteristics. This phenomenon implies the need for a mechanism that operates to segregate the identities of the two cell types throughout differentiation after initial fate commitment. To understand this mechanism, we investigated the fate specification of spinal V2a interneurons, which share important developmental genes with motor neurons (MNs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
5
38
2
Order By: Relevance
“…The generation of type I and type II V2a interneurons is analogous to motor neuron diversification in which Lhx3 is initially present in all embryonic spinal motor neurons, but subsequently it is downregulated in all subtypes except the medial motor column (Sharma et al, 1998). The overlap in Lhx3 and Chx10 ( Figure S4D) combined with previous observations that ectopic expression of Lhx3 is sufficient to induce Chx10 V2a interneuron differentiation in the dorsal spinal cord (Clovis et al, 2016;Tanabe et al, 1998;Thaler et al, 2002) suggested Lhx3 might be central to the diversification process that generates type I and type II neurons. We generated transgenic mouse lines that express these Lin11-Isl1-Mec3 (LIM) homeodomain factors in a Cre-dependent fashion (tgCAG:lsl:Lhx3 and tgCAG:lsl:Lhx4).…”
Section: Molecular and Developmental Mechanisms Underlying V2a Diverssupporting
confidence: 73%
See 1 more Smart Citation
“…The generation of type I and type II V2a interneurons is analogous to motor neuron diversification in which Lhx3 is initially present in all embryonic spinal motor neurons, but subsequently it is downregulated in all subtypes except the medial motor column (Sharma et al, 1998). The overlap in Lhx3 and Chx10 ( Figure S4D) combined with previous observations that ectopic expression of Lhx3 is sufficient to induce Chx10 V2a interneuron differentiation in the dorsal spinal cord (Clovis et al, 2016;Tanabe et al, 1998;Thaler et al, 2002) suggested Lhx3 might be central to the diversification process that generates type I and type II neurons. We generated transgenic mouse lines that express these Lin11-Isl1-Mec3 (LIM) homeodomain factors in a Cre-dependent fashion (tgCAG:lsl:Lhx3 and tgCAG:lsl:Lhx4).…”
Section: Molecular and Developmental Mechanisms Underlying V2a Diverssupporting
confidence: 73%
“…Tissue preparation, immunohistochemistry, and imaging Antibodies used were: Guinea pig anti-Chx10 (1:4000) (Thaler et al, 1999), Neurotrace-Alexa647 (life technologies, 1:100), Guinea pig anti-Vglut2 (Millipore, 1:3000), Rabbit anti-GFP (Lifetechnologies, 1:1,000), Goat anti-GFP (Millipore, 1:1,000), Rabbit anti-RFP (MBL, 1:1000), Rabbit anti-NeuN (Millipore, 1:1000), Rabbit anti-Lhx3 (1:5000) (Sharma et al, 1998), Rabbit anti-Lhx4 (1:5000) (Sharma et al, 1998), Guinea pig anti-Lhx3 (1:5,000) (Sharma et al, 1998), Guinea pig anti-Lhx4 (1:20,000) (Sharma et al, 1998), Guinea pig anti-Sox14 (Gift from the Lee lab, 1:2,000) (Clovis et al, 2016), Guinea pig anti-Shox2 (1:20,000, antibody raised against peptide sequence: PELKDRKDDAKGMEDEG), Rabbit anti-Shox2 (1:20,000, antibody raised against peptide sequence: PELKDRKDDAKGMEDEG), Goat anti-Bhlhb5 (Santa Cruz, 1:200), Rabbit anti-Nfib (Novus, 1:1,000), Sheep anti-Zfhx3 (Novus, 1:1,000), Rabbit anti-NeuroD2 (abcam, 1:1,000), Goat anti-Sp8 (Santa Cruz, 1:500).…”
Section: Methods Detailsmentioning
confidence: 99%
“…6B). At E12.5, Rnf220 mutant embryos showed a dramatic reduction in the number of spinal V2 INs, as assessed by expression of the marker proteins Chx10, Gata3, Sox14 and Lhx3 (Al-Mosawie et al, 2007;Clovis et al, 2016;Del Barrio et al, 2007;Hargrave et al, 2000;Li et al, 2005;Muroyama et al, 2005) (Fig. 7A,D).…”
Section: Abnormal Ventral Neuronal Differentiation In the Absence Of mentioning
confidence: 99%
“…3E). These targets include those encoding further TFs, such as Mnx1 in MNs and Vsx2 (also known as Chx10) in V2a neurons, that subsequently consolidate the respective neuronal identities (Arber et al, 1999;Clovis et al, 2016;Thaler et al, 1999). Neurog2 has been demonstrated to interact with LIM-HD complexes in a phosphorylation-dependent manner (Ma et al, 2008), but the sites bound by these LIM protein complexes appear to be distinct from those bound by pro-neural bHLH TFs.…”
Section: Specificity Of Neuronal Subtype Identity Is Determined By Tfmentioning
confidence: 99%